Cardiopulmonary assessment in transfusion dependent thalassemia patients at Hospital Universiti Sains Malaysia - Mohd Zain, Mohd Rizal (2007)
The thalassemias, a disease that result from mutations of genes encoding the synthesis of a.- and p-globin chains of haemoglobin are responsible for anaemia of variable severity. The P-Thalassemia is widespread throughout the Mediterranean region, Africa, the Middle East, the Indian subcontinent, Burma and Southeast Asia including southern China, the Malay Peninsula and Indonesia. Morbidity due to cardiovascular, endocrinological, and hepatic disease is considerable in P-thalassemia syndromes. Heart failure remains the major cause of death (60%), greatly exceeding deaths from the other causes such as infection (13%) and liver disease (6%). Abnormal pulmonary function tests were described in thalassemic patients who need regular blood transfusion. However this is not well described and has mixed results from the previous studies. These abnormalities could be due to anaemia, iron deposition in the lungs, or other factors. I. To describe the abnormalities in: 1.1 Cardiac function (i.e. left ventricular systolic and diastolic functions) 1.2 Respiratory function (i.e. flow rates and lung volumes) in transfusion dependent thalassemia (TOT) patients attending paediatric day care centre. 2. To determine the correlation between the abnormalities of the cardiac and the respiratory functions with serum ferritin. This is a cross sectional study, conducted at the Day Care Centre Unit, Department of Paediatrics, Hospital Universiti Sains Malaysia (HUSM) from January 2006 till December 2006. It involved all the transfusion dependent thalassemia (TOT) patients who were attending the paediatric day care centre at HUSM. A total of 41 subjects were included in this study, aged 11.4 ± 4.4 years, with the diagnosis of thalassaemia (including both alfa and beta thalassaemia). Doppler echocardiographic indexes of systolic and diastolic ventricular function were assessed. Pulmonary function test was performed using Micro loop Spirometer SPIDA and it only involved 29 subjects. This study revealed that cardiac assessment showed that when compared to the mean of normal values, there was no significant difference of LV systolic function but LV diastolic function showed significant differences and compatible with restrictive heart disease. Lung functions test showed that the majority of the patients, 26 (89. 7%) of them predominantly had restrictive lung pattern, one patient had obstructive lung pattern and only 2 of them were normal. There were no correlation of serum ferritin level with LV systolic function and diastolic function only showed weak correlation. However lung function test had no correlation at all with serum ferritin level. LV systolic perfonnance is well preserved in TOT patients despite high serum ferritin level. However diastolic dysfunction affected earlier than systolic dysfunction. Majority of TOT patients had predominantly restrictive lung pattern. Severe iron overload and deposition in the myocardium may leads to the restrictive abnormalities of left ventricular filling. However relationship between altered lung function tests and iron deposition in the lung remains unclear.